2005
DOI: 10.1143/jjap.44.3706
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Light-Emitting Properties and Different Isomers in Polymorphs of Tris(8-hydroxyquinoline) Aluminum(III) (Alq3) Analyzed by Solid-State 27Al NMR and Density Functional Theory (DFT) Calculations

Abstract: The structures of tris(8-hydroxyquinoline) aluminum(III) (Alq3) in the different polymorphs, α-, γ-, and δ-Alq3, and in the amorphous state, amo-Alq3, have been analyzed by solid-state 27Al nuclear magnetic resonance (NMR). The local structures of α- and amo-Alq3 are found to be similar; both samples are composed of the meridional isomer and are locally disordered. No evidence of the existence of the facial isomer is found even for amo-Alq3. In contrast, the isomeric states of γ- and δ-Alq3 are facial. The 27A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 37 publications
6
41
0
Order By: Relevance
“…For the two-step process, the belt-like structures were shorter, having a width of about 5 m and a length of 10-20 m. Figure 3 shows the XRD patterns for the microbelts in Figure 2. The XRD patterns for both the one-step and two-step processes have essentially the same patterns and agree with those of the -Alq 3 powders previously reported by Brinkmann et al [2], Braun et al [4], and Kaji et al [8], who confirmed that the microbelts consist of -Alq 3 regardless of the anodizing conditions. In a previous study, Katakura and Koide [10] reported that the treatment of boehmite, AlO(OH), with HQ in boiling water produces either -Alq 3 or -Alq 3 depending on whether the reaction is allowed to continue for 1 h or 90 h, respectively.…”
Section: Effect Of Anodization Process On Crystal Morphology Andsupporting
confidence: 88%
See 2 more Smart Citations
“…For the two-step process, the belt-like structures were shorter, having a width of about 5 m and a length of 10-20 m. Figure 3 shows the XRD patterns for the microbelts in Figure 2. The XRD patterns for both the one-step and two-step processes have essentially the same patterns and agree with those of the -Alq 3 powders previously reported by Brinkmann et al [2], Braun et al [4], and Kaji et al [8], who confirmed that the microbelts consist of -Alq 3 regardless of the anodizing conditions. In a previous study, Katakura and Koide [10] reported that the treatment of boehmite, AlO(OH), with HQ in boiling water produces either -Alq 3 or -Alq 3 depending on whether the reaction is allowed to continue for 1 h or 90 h, respectively.…”
Section: Effect Of Anodization Process On Crystal Morphology Andsupporting
confidence: 88%
“…Interestingly, the two isomers exhibit different types of photoluminescence (PL): specifically, green [2,3] in the case of the meridional isomer and blue [4][5][6][7] for the facial isomer. To date, five crystalline phases ( , , , , and ) have been identified for Alq 3 [8][9][10]. To the best of our knowledge, -, -, and -Alq 3 are formed by meridional isomers, whileand -Alq 3 are formed by facial isomers [2,[5][6][7][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since 1987 [2], Alq 3 has been the most extensively used light-emitting electron-transport material in organic light-emitting diodes (OLEDs), but the crystal structures of pure Alq 3 were not determined until by Brinkmann et al [3] in 2000. Until now, only eight unsolvated Mq 3 complexes have been reported including a-, b-, c-, d-, e-Alq 3 [1][2][3][4][5][6], Gaq 3 [7], Sbq 3 [8], and Inq 3 [9,10]. Table 1 lists the previously reported crystal cell unit parameters of the five phases for Alq 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The Alq 3 molecule has facial and meridianal isomers (hereinafter called fac-and mer-isomers, respectively) [1][2][3][4][5][6][7][8]. The green emission is caused by a mer-isomer, while the blue emission is caused by a fac-isomer [2,3].…”
Section: Introductionmentioning
confidence: 99%